Lamellar Lα Mesophases Doped with Inorganic Nanoparticles. Issue 7 (24th February 2014) - Constantin, Doru; Davidson, Patrick
Abstract The development of nanostructured hybrid systems is a flourishing area of research, which brings together chemistry, physics and materials science. These systems are composed of nanoparticles with interesting properties (e.g. optical, magnetic, catalytic) dispersed within an organic matrix. Control of both the position and orientation of the particles in a precise and reproducible way is an important goal. Towards this goal, the use of lyotropic liquid crystals as host phases is a promising strategy that has prompted sustained experimental work over the last decade. Here we briefly review this field, with an emphasis on the structure and the physical characterization of these novel materials.